Israel and the peace process, 1977-1982 : in search of legitimacy for peace - Bar-Siman-Tov, Yaacov, 1946- (Albany : State University of New York Press, 1994)
Annotation A theoretical study of the shift from war to peace and the acquisition of legitimacy for it, examined within the context of Israel's shift from war to peace with Egypt. The time frame of the study begins with Prime Minister Menachem Begin's accession to office in May 1977, and concludes with the final evacuation of the Sinai in April 1982. The study opens with a theoretical chapter, followed by an empirical analysis of the Israeli shift from war to peace, and finally an analysis of the empirical and theoretical implications and their relevance for the current and future negotiations in the Arab-Israeli conflict. Annotation copyright by Book News, Inc., Portland, OR.
1. Peace and Legitimacy -- 2. Begin's Rise to Power -- 3. Sadat's Initiative -- 4. Sadat's Visit to Israel -- 5. Begin's Peace Plan -- 6. Reevaluation and Negative Legitimacy -- 7. The Camp David Conference -- 8. Legitimacy for the Camp David Agreements -- 9. Crisis and Legitimacy -- 10. Implementation and Legitimacy -- 11. Evacuation and Legitimacy -- 12. Empirical and Theoretical Conclusions.
Includes bibliographical references (pages 323-329) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Israel-Arab War, 1973 -- Peace; Israel -- Foreign relations -- Egypt; Egypt -- Foreign relations -- Israel; Guerre israélo-arabe, 1973 -- Paix; Israël -- Relations extérieures -- Égypte.; Égypte -- Relations extérieures -- Israël.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Peace; Diplomatic relations; Egypt; Israel; Nahostkonflikt; Friedensbemühung; Israel; Arabisch-Israëlisch conflict; Vredespolitiek; Legitimiteit; Israël (staat); Egypte; 1973